Rheological properties of gelatine solutions for production of gluten-free pasta - Rozhno, Oleksandr; Podobiy, Olena; Yurchak, Vera (My University, 2016)
For formation of gluten-free pasta products of corn meal that does not form gluten, the selection of a structure forming substance, determining the way of its introduction and dosage on the basis of the research of the rheological properties of its solutions and impact on the quality of the goods are important.The rheological properties of colloid gelatine solutions with the concentration of 0,50-1,25%, which are prepared at the water temperature of 20°С and 40°С and the swelling duration of 40 min and at 60°С without the swelling are examined. The viscosity of these solutions is determined by the Reotest-2 viscometer at the temperature of 20°С. According to the data obtained, the rheological viscosity and fluidity curves are built and the rheological properties of the solutions are calculated. The impact of the forming substance solutions on the quality indicators of pasta products is determined. Для формування безглютенових макаронних виробів з кукурудзяного борошна, яке не утворює клейковину, важливим є вибір структуроутворювача, визначення способу його внесення та дозування на підставі вивчення реологічних властивостей його розчинів та впливу на якість виробів.Досліджено реологічні властивості колоїдних розчинів желатину концентрацією 0,50-1,25%, приготовлених за температури води 20°С та 40°С і тривалості набухання 40 хв. та за 60°С без набухання. Визначали в’язкість цих розчинів на віскозиметрі Реотест-2 за температури 20ºС. За отриманими даними будували реологічні криві в’язкості та плинності, розраховували реологічні характеристики цих розчинів.Визначено вплив розчинів структуроутворювачів на показники якості макаронних виробів.
Keywords: кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів; gelatine; кафедра технології хлібопекарських і кондитерських виробів; dosage; viscosity; желатин; дозування; в'язкість; дозировка; вязкость